4/6x-2=x-2

Simple and best practice solution for 4/6x-2=x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4/6x-2=x-2 equation:



4/6x-2=x-2
We move all terms to the left:
4/6x-2-(x-2)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
We get rid of parentheses
4/6x-x+2-2=0
We multiply all the terms by the denominator
-x*6x+2*6x-2*6x+4=0
Wy multiply elements
-6x^2+12x-12x+4=0
We add all the numbers together, and all the variables
-6x^2+4=0
a = -6; b = 0; c = +4;
Δ = b2-4ac
Δ = 02-4·(-6)·4
Δ = 96
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{96}=\sqrt{16*6}=\sqrt{16}*\sqrt{6}=4\sqrt{6}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-4\sqrt{6}}{2*-6}=\frac{0-4\sqrt{6}}{-12} =-\frac{4\sqrt{6}}{-12} =-\frac{\sqrt{6}}{-3} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+4\sqrt{6}}{2*-6}=\frac{0+4\sqrt{6}}{-12} =\frac{4\sqrt{6}}{-12} =\frac{\sqrt{6}}{-3} $

See similar equations:

| 3(3n2-43)=745 | | |5y-8|=7 | | |5y-8=7 | | 7a-3+15a+58=0 | | -37+x=-32.5 | | (X-1)(x+3)=x^2+5x-7 | | 2d=11+3d | | x(12-5)+2x=1+4x | | 7+15f=14f | | 2(4n2+17)=234 | | 2(x+8)=57.4 | | 5(4n+6)=130 | | c=5÷3 | | 5y+30=-15 | | 8(-6b+5)=-56 | | 16k^2-4(-2k^2+11k-4)=0 | | 3,330t=18 | | 9(n2+11)=180 | | 3,330÷18=t | | 22-(3c+4)=2(c+3)c | | -x^2=3x-16 | | 3,330÷t=18 | | (-4k+16k^2-4(-2k^2+11k-4))=-4 | | t÷3,330=18 | | (-4k+16k^2-4(-2k^2+11k-4)=-4 | | 6(8n-12)=168 | | (1/2)(-4k+16k^2-4(-2k^2+11k-4))=-2 | | 18=6+4w | | m-12=2184 | | (1/2)(-4k+16k^2-4(-2k^2+11k-4)=-2 | | 9(2n+6)=180 | | x+.2x=130 |

Equations solver categories